'Viewer discretion advised when preparing for surgery' – why YouTube cannot teach you how to do an upper blepharoplasty. An evaluation of the educational potential of surgical videos on blepharoplasty on YouTube. Issue 3 (1st June 2021) - Besmens, Inga S.; Uyulmaz, Semra; Knipper, Sophie; Giovanoli, Pietro; Lindenblatt, Nicole
Abstract: Over the last years, the layout of surgical training has significantly changed. Surgical residents rely on YouTube videos to prepare for upcoming cases. Eyelid surgery including blepharoplasty ranks among the 5 most often performed cosmetic surgeries. It will be one of those surgeries regularly researched by plastic surgery residents. Therefore, the aim of this study was to evaluate the educational value of the most viewed upper lid blepharoplasty videos on the most popular video broadcasting website, YouTube. A video scoring system consisting of 8 items was developed in accordance with the technical details described in the literature. Video scores were categorized into 3 groups, namely as 'poor', 'moderate; or 'good' in terms of their contribution to surgical education. The first 300 videos were evaluated for the search results for 'blepharoplasty'. After exclusion and summarization of video fragments, a total number of 36 videos were included in the study. Multivariable logistic regression models found no correlation between likes, views, comments and the attributed educational score. The quality of available educational surgical video content varies widely, and surgical trainees need to be critically aware of this as view counts as well as the number of likes and comments will not necessarily relate to videos' educational quality. There is a need for high-quality educational videos.